1959
DOI: 10.2307/3894934
|View full text |Cite
|
Sign up to set email alerts
|

A Ten-Year Study of Vegetational Changes Associated with Biological Control of Klamath Weed

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(99 citation statements)
references
References 9 publications
3
96
0
Order By: Relevance
“…Some studies that measure the strength and variability in natural enemy effects on plant populations and communities include investigations of Hypericum perforatum (Huffaker & Kennett, 1959), Senecio jacobaea (McEvoy et al, 1991), Sesbania punicea (Hoffmann & Moran, 1998), and Salvinia molesta (Room, 1990). The norm is that most outcomes of biological weed control are poorly documented: McClay (1995) reviewed 57 published papers evaluating the effectiveness of biological weed control organisms and found that attention was generally limited to monitoring the presence and spread of the agents, with little evaluation of impact on the weed and its population dynamics.…”
Section: Evidence Of Symmetry From Biological Control Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies that measure the strength and variability in natural enemy effects on plant populations and communities include investigations of Hypericum perforatum (Huffaker & Kennett, 1959), Senecio jacobaea (McEvoy et al, 1991), Sesbania punicea (Hoffmann & Moran, 1998), and Salvinia molesta (Room, 1990). The norm is that most outcomes of biological weed control are poorly documented: McClay (1995) reviewed 57 published papers evaluating the effectiveness of biological weed control organisms and found that attention was generally limited to monitoring the presence and spread of the agents, with little evaluation of impact on the weed and its population dynamics.…”
Section: Evidence Of Symmetry From Biological Control Programsmentioning
confidence: 99%
“…The classic study of H. perforatum remains one of the best demonstrations of the effects of biocontrol organisms on weed populations and plant succession (Huffaker, 1952;Huffaker & Kennett, 1959). A leaf beetle Chrysolina quadrigemina was first imported into the United States for the control of St. Johnswort (H. perforatum) in 1946.…”
Section: Paradigms Lost Paradigms Gainedmentioning
confidence: 99%
“…Historically some of the most successful biological control agents for other weeds have been defoliators (Julien and Griffiths, 1999). Examples are other leaf beetles such as Chrysolina quadrigemina (Rossi) (Coleoptera: Chrysomelidae) that controlled St. Johnswort (Hypericum perforatum L.) in California and neighboring states (Huffaker and Kennett, 1959) and two species of Galerucella that presently are controlling purple loosestrife (Lythrum salicaria L.) at several locations (Blossey et al, 2001). The exotic elm leaf beetle, Xanthogaleruca luteola (M€ u uller) (Coleoptera: Chrysomelidae), severely damages elm trees in the West (Luck and Schriven, 1976).…”
Section: Expected Results After Releasementioning
confidence: 99%
“…In some cases, rates of herbivory are higher in the light, in others, under a canopy. The classic demonstration of such an interaction is Huffaker and Kennett's (1959) study of the biological control of the introduced Klamath weed, Hypericum perforatum, in northern California by the leaf-feeding beetle, Chrysolina quadrigemina. Shortly after the beetle was introduced, Hypericum was largely eliminated from large sunny meadows where adult beetles prefer to lay their eggs, but persisted in smaller, tree-shaded refugia avoided by beetles.…”
Section: Discussionmentioning
confidence: 99%